Certification model for the institutional dimension of sustainable development - Carro Suárez, Jorge; Sarmiento Paredes, Susana; Rosano Ortega, Genoveva (Acta Universitaria, 2019)
To achieve an economic growth that preserves the natural foundations of all human activity constitutes an essential objective for organizations. Therefore, they must create a sustainable culture that is recognized as part of their institutional essence. To that end, the objective of this project was to propose a certification model of the institutional dimension of sustainable development. The methodology consisted of making a diagnosis of the perception of the institutional dimension by means of an evaluation instrument, applying inferential analysis. Based on the results obtained, a certification proposal was developed. Due to its economic relevance, the object of study was the ceramics tile industry in Tlaxcala, Mexico. The analysis revealed that organizations should monitor their activities and strengthen their participation in public policy, concluding that a certification of the institutional dimension is important for their culture to be recognized as an integral part of their sustainability.